Modelling the Impact of Travel Time Uncertainty to the Cocoa Supply Chain Network - Febri Zukhruf; Russ Bona Frazila (Jurnal Teknik Sipil, 2018)
AbstractThe uncertainty issue becoming more and more important in term of freight transport, which essentially affect the transport cost. As an essential parameter to construct the product price, the transport cost variations sequentially impact the supply chain network structures. This paper then presents the multi-channelled supply chain network equilibrium (SCNE) model with the behaviour of freight carriers by considering variation of travel time. The cocoa SCNE model is then invoked to represent the trading chain of cocoa. As different with the previous researches, the model takes into account the variation of traffic flow and the road capacity to the freight cycle time, which is practically used for estimating the transport cost. The variation is propagated based on the Monte Carlo simulation approach. Finally, the model is applied to an actual cocoa SCN in Sulawesi for investigating the impact of travel time variation to the price of cocoa.AbstrakKetidakpastian di dalam jaringan transportasi menjadi isu yang semakin penting di dalam dunia angkutan barang, yang secara subtantif dapat mempengaruhi komponen biaya transportasi. Sebagai parameter penting untuk membangun harga produk, variasi biaya transportasi berperan dalam mempengaruhi struktur jaringan rantai pasokan. Makalah ini kemudian mendiskusikan model supply chain network equilibrium (SCNE) dengan perilaku angkutan barang dengan mempertimbangkan variasi waktu tempuh. Cocoa SCNE model kemudian digunakan untuk mewakili rantai pasok komoditas kakao. Berbeda dengan penelitian sebelumnya, makalah ini memperhitungkan variasi arus lalu lintas dan kapasitas jalan terhadap waktu siklus pengiriman, yang secara praktis digunakan untuk memperkirakan biaya transportasi. Variasi tersebut dibangun dengan mendasarkan kepada pendekatan simulasi Monte Carlo. Akhirnya, model ini diterapkan pada jaringan rantai pasok kakao di Sulawesi untuk menyelidiki dampak variasi waktu tempuh terhadap harga kakao.